Traffic jam within lymphocytes: A clinician’s perspective - Hosahalli Vasanna, Smitha; Dalal, Jignesh (Frontiers in Immunology, 2023)
With the discovery of novel diseases and pathways, as well as a new outlook on certain existing diseases, cellular trafficking disorders attract a great deal of interest and focus. Understanding the function of genes and their products in protein and lipid synthesis, cargo sorting, packaging, and delivery has allowed us to appreciate the intricate pathophysiology of these biological processes at the molecular level and the multi-system disease manifestations of these disorders. This article focuses primarily on lymphocyte intracellular trafficking diseases from a clinician’s perspective. Familial hemophagocytic lymphohistiocytosis is the prototypical disease of abnormal vesicular transport in the lymphocytes. In this review, we highlight other mechanisms involved in cellular trafficking, including membrane contact sites, autophagy, and abnormalities of cytoskeletal structures affecting the immune cell function, based on a newer classification system, along with management aspects of these conditions.